The efficacy of core stabilization exercise in mild and moderate adolescent idiopathic scoliosis: a systematic review and meta-analysis - Xiaomei Liu; Yanyang Wang; Min Liu; Yu Zhang; Qiang Wu; Qian Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Adolescent idiopathic scoliosis (AIS) is one of the most prevalent spinal abnormalities. Core stabilization exercise (CSE) has become a common approach in the treatment of AIS. However, the efficacy of CSE in AIS remains a subject of debate. Objective To determine the efficacy of CSE in the patients with AIS in comparison with different intervention programs. Methods A comprehensive search was conducted across PubMed, Embase, The Cochrane Library, Web of Science, Wan Fang, Wei Pu, and CNKI databases, encompassing literature from their inception through December 31st, 2024. Two independent reviewers screened the studies, with inter-rater agreement evaluated via kappa scores. Randomized control trials that focus on the efficacy and safety of CSE in AIS population were included in this systematic review. The risk of bias assessment was performed utilizing the National Institutes of Health Quality Assessment Tools (NIH-QAT). After quality assessments and information extraction, the meta-analysis was conducted with Review manager and the standard mean difference (SMD) was pooled among the measurement data derived from different studies. Cobb angle, angle of trunk rotation, apical vertebral rotation, Walter Reed Visual Assessment Scale, Posterior Trunk Symmetry Index, forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1/FVC, SRS-22,, were focused as outcomes. Results A total of 10 studies involving 449 subjects were included in this systematic review. The average Cobb angle was 22.86° ± 8.79°, and the intervention duration varied from 8weeks to 6months. The kappa score was 0.93. Subgroup analyses were performed based on the different control groups, National Institutes of Health Quality Assessment Tools (NIH-QAT) results, and intervention durations. The results indicated that CSE could have greater effect sizes than the blank control group on Cobb angle (MD = -4.37, P < 0.05), angle of trunk rotation (MD = -1.07, P < 0.05), apical vertebral rotation (MD = -0.44, P < 0.05), quality of life as SRS-22 (MD = 0.22, P < 0.05). Notably, the efficacy of CSE appears to be weaker than that of the three-dimensional exercise group in terms of Cobb angle (MD = 3.95, P < 0.05), angle of trunk rotation (MD = 1.69, P < 0.05) and WASRS scores (MD = 0.89, P < 0.05). Other subgroup analyses yielded no statistically significant differences. Conclusions The present study showed that core stabilization exercise may be beneficial for the patients with mild to moderate adolescent idiopathic scoliosis, albeit less effective than three-dimensional exercises following short-term follow-up. The evidence on the efficacy of CSE is limited due to heterogeneity, small sample sizes, and multiple comparisons. The clinical trials focusing on patient compliance and training quality with long-term follow-up are warranted. PROSPERO registration number CRD 42022367714.